Structures of Acid B and Related Compounds, Oxidation Products of Lycoramine - KOIZUMI, JUNJI; IMAKURA, YASUHIRO; TOKUMOTO, TOSHIHIRO; SHINGU, TETSURO; KIHARA, MASARU; KOBAYASHI, SHIGERU; UYEO, SHOJIRO (Chemical & pharmaceutical bulletin, 1986)
The structures of "acid B" and its monoethyl ester, which are stepwise oxidation products of lycoramine (2), an Amaryllidaceae alkaloid, and the structure of a nitro derivative of acid B, an oxidation product of oxolycoramine (5) with nitric acid, were established as 6, 10 and 12, respectively, on the basis of spectral and chemical evidence.